PWE-147 Human Herpesvirus and Adenovirus Unique Genetic Sequences Detected in Hepatocellular Cancer Genomes. (4th June 2013) - Fateen, W; Berri, S; Wood, H; Morgan, J; Taylor, G; Quirke, P
Abstract : Introduction: Hepatitis C virus (HCV) is the most common cause of hepatocellular cancer (HCC) in the western world. HCV is an RNA virus that does not integrate with human DNA and so the oncogenic mechanisms of HCV remain unclear. Next generation sequencing (NGS) provides a flexible platform and generates large amounts of data at a relatively small time and constantly reducing costs. The role of viral infection is well established in the aetiology of a wide range of tumours. In this study we investigate DNA of HCV driven HCC for the possibility of integration of all known viral genomes. Methods: Bar-coded DNA libraries from 41 samples of various stages of development of HCC from 6 different patients were sequenced in parallel using NGS. One to two million 74bp reads per genome were generated. The reads were aligned to all known viral genomes downloaded from the National Center for Biotechnology Information using Burrows-Wheeler Aligner (BWA). Reads with mapping scores of < 37 were discarded. Basic Local Alignment Search Tool (BLAST) was used to test if the sequences that aligned to viral genomes belonged to the human genome or any other viruses apart from the identified virus. Only those reads were the BWA alignment matched the leading BLAST hit were considered Results: Six test samples mapped to unique sequences from Human herpesvirus 6. The test samples included a single HCC and 5 pre-malignant nodules from 2 different patients. Six test samples mapped to unique sequences of Human Adenovirus (6/41). The test samples in this case included 4 HCCS and a 2 premalignant nodules from 2 different patients. A single dysplastic nodule mapped to Human papillomavirus. Conclusion: DNA from HCV driven HCC was searched for all viral genome sequences only Human Herpes 6, Human Adenovirus and Human pappilomavirus were found in a small number of cases. Further studies are needed to understand their relation to HCV hepatocarcinogenesis. Disclosure of Interest: None Declared.